Review of Nairobi Urban Agriculture Policy: Final External Stakeholders Convening - Onyango, E. (2025)
The final External Stakeholders Convening was held at Movenpick Hotel, Nairobi, August 25, 2025. The meeting brought together 77 external stakeholders from Youth in Agribusiness, Civil Society Organisations, Non-governmental Organizations, Private Sector, Academia, State actors, County Governments, urban farmers and market traders, independent consultants in Food Systems, and the co-hosts, the Partnership for Social and Governance Research (PASGR). The objective of the meeting was to sensitize the external stakeholders on the Urban Agriculture Policy and receive stakeholders’ views/inputs for consideration into policy before public participation. The Food Systems Transformation Project (FST) seeks to promote sustainable food systems by enhancing the capacity for policy engagement and evidence uptake targeted to strategic stakeholders. The aim of the convening was to engage external stakeholders, following the previous internal stakeholders convening to give their views concerning the UAP. Furthermore, facilitate dialogue with strategic external stakeholders on interventions needed to advance food system transformation. The participation of external stakeholders was vital, as their views on the UAP play a key role in shaping the policy process.